2014
DOI: 10.1111/nyas.12429
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor agonists’ anti‐inflammatory properties

Abstract: One century after its discovery, vitamin D has been shown to be, in fact, a pleiotropic steroid hormone, which, besides regulation of calcium homeostasis and bone turnover, has antiproliferative, prodifferentiation, antibacterial, immunomodulatory, and anti-inflammatory properties in various cells and tissues. D hormone (1α,25(OH)2 D), regulated in an endocrine, autocrine, and paracrine manner, must be bound to the specific nuclear vitamin D receptor (VDR) to exert epigenetic and genetic effects, acting as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 84 publications
(144 reference statements)
0
26
0
2
Order By: Relevance
“…An experimental study in which rats with hepatic steatosis received cholecalciferol reported improved cognitive effects and reduced TNF-a levels in brain [33]. Therefore, the observed benefits may have resulted from the anti-inflammatory properties of vitamin D [34], a finding that supports the inflammatory hypothesis for some types of depression.…”
Section: Discussionmentioning
confidence: 81%
“…An experimental study in which rats with hepatic steatosis received cholecalciferol reported improved cognitive effects and reduced TNF-a levels in brain [33]. Therefore, the observed benefits may have resulted from the anti-inflammatory properties of vitamin D [34], a finding that supports the inflammatory hypothesis for some types of depression.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, vitamin D is recognized for its non-classical actions including the modulation of innate immune and the regulation of cell proliferation1920. Indeed, vitamin D is a potent anti-inflammatory agent212223. Vitamin D itself is devoid of biological activity.…”
mentioning
confidence: 99%
“…Besides the mineral metabolism, it has anti-inflammatory effects [4, 5]. Studies of cultured cells and animal models have shown that 1,25D 3 attenuates the effects of LPS.…”
Section: Introductionmentioning
confidence: 99%